The Principal's Self-Leadership Through The Peer Foster Student Innovation Program In Improving The Quality Of Schools - Argadinata, Hasan; Supriyanto, Achmad; Mustiningsih, Mustiningsih (International Research-Based Education Journal, 2023)
The purpose of this study is to determine self leadership through peer care student programs in an effort to improve the quality of education in elementary schools.To answer the topic raised, researchers choose research using a qualitative approach because researchers want to know in depth about the phenomena that actually occur inschools. In the process of data analysis researchers used NVivo's analysis tools to find output from in-depth interview transcripts, field notes, and documentationstudies. Self-leadership is in the principal who is supported by his emergence with 1) Urgency, 2) Employee Commitment, 3) Creativity, 4) Interdependence, and 5)Complexity